Late Pennsylvanian vegetation dynamics of the Donets Basin, Ukraine - Nataliya Boyarina (Geo&Bio)
The dynamics of the Late Pennsylvanian vegetation cover of the Donets Basin is represented by a succession of formations of new plant communities (phytocoenogenesis) of a wetland forest and woodland biome and a seasonally dry woodland biome because of the changing landscape and climate conditions resulting from the glacio-eustatic changes during the Late Paleozoic Ice Age. The Late Pennsylvanian vegetation consisted of plant communities of wetland marattialean fern-dominated forests on coastal lowlands and wetland lycopsid-fern forests on deltaic plains in the Kasimovian as well as wetland marattialean fern-dominated forests with new dominants on coastal lowlands and wetland lycopsid-pteridosperm-calamitalean-fern forests with new dominants on deltaic plains in the early Gzhelian that were formed according to the evolutionary progressive model of phytocoenogenesis under conditions of an expansion of coastal lowlands and deltaic plains inthe long-term period of a relatively stable higher sea level with frequent sea level fluctuations during the late Kasimovian–early-mid-Gzhelian interglacial interval. The subsequent transformation of wetland forests to wetland woodlands on coastal lowlands and deltaic plains according to the substitutionary regressive model of phytocoenogenesis and the formation of the new seasonally dry peltaspermalen pteridosperm-dominated woodland communities in river valleys according to the evolutionary progressive model of phytocoenogenesis took place against the background of a reduction of coastal lowlands and an expansion of river landscapes in the long-term period of a relatively stable sea level drop during the early phase of the late Gzhelian glacial interval. The new plant communities of wetland calamitalean-fern-pteridosperm woodlands on coastal lowlands and seasonally dry fern-pteridosperm woodlands on lagoon coasts in the late Gzhelian were formed according to the migration progressive model of phytocoenogenesis due to a migration of plants from reduced river landscapes to coastal lowlands and lagoon coasts in the period of the further sea level drop with low-amplitude sea level oscillations and an increased drying during the continued late Gzhelian glacial interval.